NMD abnormalities during brain development in the Fmr1-knockout mouse model of fragile X syndrome - Tatsuaki Kurosaki; Hitomi Sakano; Christoph Pröschel; Jason Wheeler; Alexander Hewko; Lynne E. Maquat (Genome Biology, 2021)
Abstract Background Fragile X syndrome (FXS) is an intellectual disability attributable to loss of fragile X protein (FMRP). We previously demonstrated that FMRP binds mRNAs targeted for nonsense-mediated mRNA decay (NMD) and that FMRP loss results in hyperactivated NMD and inhibition of neuronal differentiation in human stem cells. Results We show here that NMD is hyperactivated during the development of the cerebral cortex, hippocampus, and cerebellum in the Fmr1-knockout (KO) mouse during embryonic and early postnatal periods. Our findings demonstrate that NMD regulates many neuronal mRNAs that are important for mouse brain development. Conclusions We reveal the abnormal regulation of these mRNAs in the Fmr1-KO mouse, a model of FXS, and highlight the importance of early intervention.